Ligand-based virtual screening for the discovery of inhibitors for protein arginine deiminase type 4 (PAD4) - Teo, Chian Ying; Abdul Rahman, Mohd Basyaruddin; Leow, Adam Thean Chor; Salleh, Abu Bakar; Ballester, Pedro J.; Tejo, Bimo Ario (OMICS International, 2013)
Protein Arginine Deiminase type 4 (PAD4) is a new therapeutic target for the treatment of rheumatoid arthritis. In this study, ligand-based virtual screening with the integration with drug repurposing strategy was applied to the discovery of PAD4 inhibitors. Ultrafast Shape Recognition (USR) was used to search for compounds with similar shape to a previously reported inhibitor with harmful side-effects, i.e., streptonigrin. Thirty five lead-like compounds and two existing drugs were obtained from virtual screening and their inhibitory activity was tested at fixed concentration of 100 μM. Five lead-like compounds showed significant inhibition on the enzymatic activity of PAD4. The potency of the best compound was investigated by carrying out IC50 study. Importantly, the structure of the best of these new active molecules was strikingly different from that of streptonigrin. Furthermore, this new PAD4 inhibitor is the most potent to date found by a computational approach and its structure can be optimized in the future for the design of an even better inhibitor of PAD4.